2022
DOI: 10.3390/ma15051809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intercooling Intensity on Temperature Field and Microstructure of Large-Scale 2219 Al Alloy Billet Prepared by Internal Electromagnetic Stirring Casting

Abstract: Internal electromagnetic stirring is an advanced melt treatment method, which can be used in direct chill casting to prepare large-scale Al alloy billets. Intercooling intensity is a primary parameter of internal electromagnetic stirring; its effects on temperature fields and microstructures have been investigated via numerical simulations and industrial experiments, respectively. The simulated results show an increase in the intercooling affected area and a decrease in sump depth with an increase in the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…A mush , U cast , f L , and f S denote the constants related to the mushy zone, casting velocity, liquidphase fraction, and solid-phase fraction, respectively. k P , T S , T L , and T m represent the solute partition coefficient, solidus line, liquidus line, and melting point, respectively [18]. Energy equation:…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mush , U cast , f L , and f S denote the constants related to the mushy zone, casting velocity, liquidphase fraction, and solid-phase fraction, respectively. k P , T S , T L , and T m represent the solute partition coefficient, solidus line, liquidus line, and melting point, respectively [18]. Energy equation:…”
Section: Governing Equationsmentioning
confidence: 99%
“…Therefore, numerical simulation has become a viable alternative method [17]. Qiu et al [18] conducted a simulation to investigate the influence of cooling intensity on the casting process in 2219 aluminum alloy using the internal electromagnetic stirring technique. The simulation results revealed that increasing the intercooling heat transfer coefficient expanded the affected region by intercooling.…”
Section: Introductionmentioning
confidence: 99%